The importance of academicians' involvement in community service - Mohd Noor, Mohd. Nazri; Laton, Mohd Zahid; Abdul Razak, Muhammad Azmir (Universiti Teknologi MARA, 2009)
The aim of this paper is to highlight the importance of academicians' involvement in community service. Undisputedly, strategic partnership in community service offers numerous benefits to academicians, universities and community groups. For those reasons, the focal point of this paper is to recognise the three major thrusts of community service, that is, the benefits and impacts of the service on 1) the academicians themselves, 2) the university, and 3) the community groups. It is found that community service is able to develop skills and enhance morale among academicians, reinforces the corporate image of a particular university and most importantly, contributes to breaking down barriers between community and university. This paper clearly signifies numerous reasons why it is essential for academicians to comprehend that in this day and age, community service is no longer an option to them. As a final point, this paper also highlights evidence that indicates communities now have higher expectations towards the university establishment than before. Thus, universities should now think of themselves as part of the community and should actively encourage their academicians to be actively involved in community service.